(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2021)
Background: Chronic otitis media with ossicular discontinuity is most commonly faced otological condition which causes conductive hearing loss. It presents mostly with ear discharge and decreased hearing. The use of cartilage graft material in ossiculoplasty markedly improve the result in hearing. In this study we have used autologous (tragal/conchal) cartilage or homologous (septal) cartilage for ossiculoplasty and temporalis fascia graft for tympanoplasty. Aims: Aim of the study was to compare and analyze the outcome of ossiculoplasty using autologous conchal/tragal cartilage and homologous septal cartilage in terms of hearing results and graft uptake rates. Materials and method: The study was conducted in E.N.T. Department at S.C.L. Hospital, NHLMMC Ahmedabad. 50 patients were randomly selected and divided in 2 groups. 25 patients underwent homologous and 25 patients underwent autologous cartilage reconstruction. All patients underwent detailed ENT examination followed by audiological and radiological assessment of temporal bone, and those patients with evidence of ossicular erosion were subjected to ossiculoplasty with autologous cartilage and homologous cartilage randomly. Results: Majority of the patients have central perforation and retraction pockets in middle ear pathology in both groups. Overall graft taken up rate was 96% in autologous while 92% in homologous ossiculoplasty. Our study shows hearing improvement up to 20-25 dB in 80% and 88% in autologous and homologous ossiculoplasty. Conclusion: Both autologous and homologous cartilage have excellent outcomes and gives equivalent results irrespective of age or sex of the patient or middle ear pathology. In both the groups hearing improvement is similar. Subjective hearing is also improved. No post-op complications like wound infection, facial palsy, dead ear have occurred in either case.